A thick bondline beam model for the adhesively bonded 3-point bending specimen. (January 2020) - de Morais, A.B.
Abstract: The adhesively bonded 3-point bending specimen has been recently considered for evaluating the adhesive shear stress-strain behaviour. Its main advantage is avoiding the spurious end effects typical of lap-joints. A previous beam model proved to be fairly accurate for thin bondlines typical of structural joints. The present study extends such model to thick bondlines and achieves improved shear strain results. Model predictions were in very good agreement with finite element analyses of specimens with metal adherends and adhesive elastic-perfectly plastic behaviour. The present model will facilitate the inverse method needed to evaluate the parameters of a piecewise linear approximation to the adhesive shear stress-strain curve. Furthermore, two simplified models were shown to provide useful bounds for the shear stress-strain curve using only the basic load-displacement data.